6-Amino-3,4-dimethyl-1,2,4-triazin-1-ium 2-anilinobenzoate–3-amino-5,6-dimethyl-1,2,4-triazine (1/1) - Sangeetha, Ramalingam; Balasubramani, Kasthuri; Thanigaimani, Kaliyaperumal; Razak, Ibrahim Abdul (International Union of Crystallography, 2017)
In the title molecular salt, C5H9N4+.C13H10NO2-.C5H8N4, the asymmetric unit consists of a 6-amino-3,4-dimethyl-1,2,4-triazin-1-ium cation, a 2-anilinobenzoate anion and a neutral 3-amino-5,6-dimethyl-1,2,4-triazine molecule. The typical intramolecular N...H—O hydrogen bond is observed in the 2-anilinobenzoate anion. In the crystal, the protonated N atom and the 3-amino group are hydrogen bonded to the carboxylate oxygen atoms via a pair of N— H...O hydrogen bonds, forming an R2/2 (8) ring motif. These motifs are further linked with adjacent neutral 3-amino-5,6-dimethyl-1,2,4-triazine molecules by N—H...O and N—H...N hydrogen bonds to produce centrosymmetric sixmembered units, enclosing R2/2(8) and R3/4(9) ring motifs. They are reinforced by a C—H...N hydrogen bond and stack up the b-axis direction.